The role of guilt and pride in consumers’ self-regulation: an exploration on sustainability and ethical consumption - Antonetti, Paolo (Cranfield University, 2012)
Researchers are interested in understanding the individual processes that favour consumers’ self-regulation since they can contribute to the achievement of personal and collective long-term goals in many areas. Sustainable and ethical consumption represents one such context; self-regulation can be a key driver for the solution of environmental and social sustainability challenges. In a series of three studies, this thesis investigates how guilt and pride contribute to consumers’ decisions to purchase sustainable products. The research adopts a multiple methods approach. The first qualitative study explores the process that leads to emotional experiences and describes what characterises feelings of guilt and pride. Five key dimensions that lead to enhanced self-control and stronger experiences of guilt and pride are identified: 1) altruistic value preference, 2) moral relevance of the issue presented, 3) credibility of the ethical claim(s) presented, 4) perception of a trade-off between altruism and self-interest, 5) social visibility of the decision. The two quantitative investigations examine consumers’ emotional reactions and how they affect future intentions to purchase sustainable products. It is demonstrated that: 1) feelings of guilt and pride have a positive influence on the intentions to purchase ethical products in the future; 2) intentionality is not necessary to experience guilt or pride; 3) experiences of guilt and pride have a positive impact on consumers’ efficacy beliefs; 4) beliefs in self-efficacy and collective efficacy influence positively intentions to purchase ethical products in the future. This research contributes to the literature on sustainable consumption by exploring how guilt and pride influence the purchase of ethical alternatives. This thesis also contributes to other domains of consumer research by: 1) explaining how guilt and pride influence cognition in self-regulation contexts; 2)developing a context-bound theory of appraisal in the study of guilt and pride. Implications for practitioners are also critically discussed.